Chiral δ-iodo-γ-lactones derived from cuminaldehyde, 2, 5-dimethylbenzaldehyde and piperonal: chemoenzymatic synthesis and antiproliferative activity. Issue 6 (1st April 2016) - Gładkowski, Witold; Skrobiszewski, Andrzej; Mazur, Marcelina; Gliszczyńska, Anna; Czarnecka, Marta; Pawlak, Aleksandra; Obmińska-Mrukowicz, Bożena; Maciejewska, Gabriela; Białońska, Agata
Graphical abstract: Abstract: Six enantiomeric pairs of β-aryl-δ-iodo-γ-lactones8a –c, 9a –c derived from cuminaldehyde, 2, 5-dimethylbenzaldehyde and piperonal were synthesized with high enantiomeric purities (ee 93–99%) from enantiomerically enriched allyl alcohols3a –c . The key step in the synthesis of lactones8a and9a was the kinetic resolution of racemic ( E )-4-(4′-isopropylphenyl)but-3-en-2-ol3a by a lipase-catalysed transesterification. Among the five tested enzymes, the most effective and enantioselective was lipase B from Candida antarctica and after 2 h (−)-( S )-alcohol3a and (+)-( R )-propionate5 were obtained with ee's ⩾99%. The transfer of chirality from alcohols ( S )-3a –c and ( R )-3a –c to γ, δ-unsaturated esters ( S )-6a –c and ( R )-6a –c via a stereoselective Johnson–Claisen rearrangement followed by hydrolysis and iodolactonization afforded the final lactones8a –c and9a –c . The configurations of their stereogenic centres were assigned based on crystallographic analysis and/or the iodolactonization mechanism. In 42 of 48 tests, the synthesized lactones showed antiproliferative activity against four selected cancer lines (Jurkat, D17, GL-1, CLBL-1). The trans -stereoisomers were more active than the cis -stereoisomers and the highest activity was found for lactone (−)- trans -(4 S, 5 R, 6 S )-9c with a 1, 3-benzodioxole substituent and both enantiomers of the trans -lactone with a 2, 5-dimethylphenyl substituent: (+)-9b and (−)-9b . Among the trans -lactones, those with a (4 S, 5 R, 6 S )-configuration exhibited higher activity than their enantiomers and the most significant difference was observed for the enantiomers of the trans -lactone with a 1, 3-benzodioxole substituent9c (IC50  = 5.29 and 5.08 vs 36.47 and 33.77 for Jurkat and GL-1 cancer lines respectively). Abstract : (−)-(2 S, 3 E )-4-(4′-Isopropylphenyl)but-3-en-2-ol: C13 H18 O Ee = 99% [ α ]D 20  = −24.0 ( c 5.4, CH2 Cl2 ) Source of chirality: enzyme-mediated kinetic resolution Absolute configuration: ( S ) Abstract : (+)-(2 R, 3 E )-4-(4′-Isopropylphenyl)but-3-en-2-yl propionate: C16 H22 O2 Ee > 99% [ α ]D 20  = +109.8 ( c 1.6, CH2 Cl2 ) Source of chirality: enzyme-mediated kinetic resolution Absolute configuration: ( R ) Abstract : (+)-(3 S, 4 E )-3-(4′-Isopropylphenyl)hex-4-enoic acid ethyl ester: C17 H24 O2 Ee = 99% [ α ]D 20  = +8.3 ( c 4.0, CH2 Cl2 ) Source of chirality: (−)-(2 S, 3 E )-4-(4′-Isopropylphenyl)but-3-en-2-ol Absolute configuration: ( S ) Abstract : (+)-(3 S, 4 E )-3-(2′, 5′-Dimethylphenyl)hex-4-enoic acid ethyl ester: C16 H22 O2 Ee = 99% [ α ]D 20  = +22.1 ( c 1.2, CH2 Cl2 ) Source of chirality: (−)-(2 S, 3 E )-4-(2′, 5′-Dimethylphenyl)but-3-en-2-ol Absolute configuration: ( S ) Abstract : (−)-(3 S, 4 E )-3-(Benzo[ d ][1′, 3′]-dioxol-5′-yl)hex-4-enoic acid ethyl ester: C15 H18 O4 Ee = 99% [ α ]D 20  = −2.5 ( c 0.7, CH2 Cl2 ) Source of chirality: (−)-(2 S, 3 E )-4-(Benzo[ d ][1′, 3′]dioxol-5′-yl)but-3-en-2-ol Absolute configuration: ( S ) Abstract : (+)-(3 S, 4 E )-3-(4′-Isopropylphenyl)hex-4-enoic acid: C15 H20 O2 Ee = 99% [ α ]D 20  = +7.8 ( c 1.7, CH2 Cl2 ) Source of chirality: (+)-(3 S, 4 E )-3-(4′-Isopropylphenyl)hex-4-enoic acid ethyl ester Absolute configuration: ( S ) Abstract : (+)-(3 S, 4 E )-3-(2′, 5′-Dimethylphenyl)hex-4-enoic acid: C14 H18 O2 Ee = 99% [ α ]D 20  = +23.0 ( c 1.5, CH2 Cl2 ) Source of chirality: (+)-(3 S, 4 E )-3-(2′, 5′-Dimethylphenyl)hex-4-enoic acid ethyl ester Absolute configuration: ( S ) Abstract : (−)-(3 S, 4 E )-3-(Benzo[ d ][1′, 3′]-dioxol-5′-yl)hex-4-enoic acid: C13 H14 O4 Ee = 99% [ α ]D 20  = −7.4 ( c 0.1, CH2 Cl2 ) Source of chirality: (−)-(3 S, 4 E )-3-(Benzo[ d ][1′, 3′]-dioxol-5′-yl)hex-4-enoic acid ethyl ester Absolute configuration: ( S ) Abstract : (+)- cis -(4 R, 5 R, 6 S )-5-(1-Iodoethyl)-4-(4′-isopropylphenyl)dihydrofuran-2-one: C15 H19 IO2 Ee = 99% [ α ]D 20  = +1.9 ( c 0.8, CH2 Cl2 ) Source of chirality: (+)-(3 S, 4 E )-3-(4′-Isopropylphenyl)hex-4-enoic acid Absolute configuration: (4 R, 5 R, 6 S ) Abstract : (−)- trans -(4 R, 5 S, 6 R )-5-(1-Iodoethyl)-4-(4′-isopropylphenyl)dihydrofuran-2-one: C15 H19 IO2 Ee = 99% [ α ]D 20  = −8.5 ( c 1.7, CH2 Cl2 ) Source of chirality: (+)-(3 S, 4 E )-3-(4′-Isopropylphenyl)hex-4-enoic acid Absolute configuration: (4 R, 5 S, 6 R ) Abstract : (−)- cis -(4 R, 5 R, 6 S )-5-(1-Iodoethyl)-4-(2′, 5′-dimethylphenyl)dihydrofuran-2-one: C14 H17 IO2 Ee >99% [ α ]D 20  = −31.1 ( c 0.8, CH2 Cl2 ) Source of chirality: (+)-(3 S, 4 E )-3-(2′, 5′-Dimethylphenyl)hex-4-enoic acid Absolute configuration: (4 R, 5 R, 6 S ) Abstract : (+)- trans -(4 R, 5 S, 6 R )-5-(1-Iodoethyl)-4-(2′, 5′-dimethylphenyl)dihydrofuran-2-one: C14 H17 IO2 Ee = 99% [ α ]D 20  = +14.6 ( c 0.3, CH2 Cl2 ) Source of chirality: (+)-(3 S, 4 E )-3-(2′, 5′-Dimethylphenyl)hex-4-enoic acid Absolute configuration: (4 R, 5 S, 6 R ) Abstract : (−)- cis -(4 R, 5 R, 6 S )-5-(1-Iodoethyl)-4-(benzo[ d ][1′, 3′]-dioxol-5′-yl)dihydrofuran-2-one: C13 H13 IO4 Ee >99% [ α ]D 20  = −4.8 ( c 0.10, CH2 Cl2 ) Source of chirality: (−)-(3 S, 4 E )-3-(Benzo[ d ][1′, 3′]-dioxol-5′-yl)hex-4-enoic acid Absolute configuration: (4 R, 5 R, 6 S ) Abstract : (+)- trans -(4 R, 5 S, 6 R )-5-(1-Iodoethyl)-4-(benzo[ d ][1′, 3′]-dioxol-5′-yl)dihydrofuran-2-one: C13 H13 IO4 Ee >99% [ α ]D 20  = +7.4 ( c 0.2, CH2 Cl2 ) Source of chirality: (−)-(3 S, 4 E )-3-(Benzo[ d ][1′, 3′]-dioxol-5′-yl)hex-4-enoic acid Absolute configuration: (4 R, 5 S, 6 R )